2004
DOI: 10.1634/stemcells.22-5-716
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Maintenance of Human Cord Blood SCID‐Repopulating Cells and Expansion of Committed Progenitors at Low O 2 Concentration (3%)

Abstract: The transplantation of unmanipulated cord blood (CB) cells has two major disadvantages: (a) the low number of hematopoietic stem and progenitor cells (colony-forming cells [CFCs]) in each harvest limits its application to children, and (b) there is a long period (30 days) of post-transplantation cytopenia [1]. Simultaneous ex vivo amplification of the CFCs and primitive stem cells could resolve both problems. Extensive ex-pansion of nonobese diabetic/severe combined immuno-deficiency (NOD/SCID) mice-repopulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
113
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 35 publications
10
113
1
Order By: Relevance
“…Indeed, severe hypoxia enhances maintenance in vitro of normal stem cells capable of short-term hematopoietic reconstitution (STR-HSC). This finding was later confirmed for human long-term repopulating (LTR) stem cells reconstituting NOD/ SCID mice [6,7]. We also showed that hypoxia protects stem cells from stimuli that induce lineage commitment to differentiation [5].…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…Indeed, severe hypoxia enhances maintenance in vitro of normal stem cells capable of short-term hematopoietic reconstitution (STR-HSC). This finding was later confirmed for human long-term repopulating (LTR) stem cells reconstituting NOD/ SCID mice [6,7]. We also showed that hypoxia protects stem cells from stimuli that induce lineage commitment to differentiation [5].…”
Section: Introductionsupporting
confidence: 58%
“…This study was based on the adaptation to leukemia cells [11,12] of the CRA assay developed in our laboratory [2] and successfully applied [3,5,7,13] for the quantification in vitro of the stem cell potential of normal hematopoietic cell populations. The CRA assay, in combination with incubation under severe hypoxia as a selection procedure, showed that the MEL cell population includes highly hypoxia-sensitive CFC as well as their hypoxia-resistant, CRC-type progenitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have suggested that long term HSCs reside mainly in the endosteal sites of the BM, in which the pO 2 is very low (3,6). Cell biological studies using HS(P)Cs indicated that their functions as well as their quiescence state are maintained most effectively under hypoxic conditions (10,(47)(48)(49)(50)(51)(52). Hypoxia stabilizes the HIF-1␣ protein, a master regulator of oxygen homeostasis, and activates HIF-1␣-mediated signals in HSCs (48,53,54).…”
Section: Discussionmentioning
confidence: 99%